Novel POMGNT1 point mutations and intragenic rearrangements associated with muscle-eye-brain disease - Saredi, S. (Elsevier, 2012)
Congenital muscular dystrophies due to defects in genes encoding proteins involved in α-dystroglycan (α-DG) glycosylation are a heterogeneous group of muscle disorders variably associated with central nervous system and eye abnormalities. One of the more severe is muscle-eye-brain disease (MEB). Mutations in genes coding for proven or putative glycosyltransferases (POMT1, POMT2, POMGnT1, fukutin, FKRP, and LARGE), the DPM3 gene encoding a DOL-P-Man synthase subunit, and the DAG1 gene encoding α-dystroglycan, have been associated with altered α-DG glycosylation. We report new POMGnT1 mutations and evaluate protein expression in 3 patients and 2 foetuses with variably severe MEB features. We identify two new point mutations (c.643 C > T, c.1863delC), one new intragenic rearrangement (deletion of exons 2–8), and a new intron retention (between exons 21 and 22) resulting from a known point mutation c.1895 + 1 G > T. Our study provides further evidence that rearrangements of the POMGnT1 gene are relatively common. Importantly, if heterozygous, they can be missed on standard genomic DNA sequencing. POMGNT1 protein analysis in 3 patients showed that the severity of the phenotype does not correlate with protein expression. Cerebral MRI is important for identifying MEB and α-dystroglycanopathy phenotypes in children and foetuses, and hence for directing the genetic analysis.